Analisis Perbedaan Kinerja Keuangan Perusahaan Antara Sebelum Dan Sesudah Berpartisipasi Dalam Indonesia Sustainability Reporting Awards (ISRA) - Megi Oktriani Herman; Randy Heriyanto (Akuntansi dan Manajemen, 2017)
This study discusses the importance of corporate funding between before and after agreeing to the ISRA. This study uses secondary data. The variables in this study are financial in terms of profitability ratios that use returns on assets (ROA), return on equity (ROE), net profit margin (NPM). The study sample consisted of 13 companies with a purposive sampling method, namely a company that was the participant of the Indonesian Sustainability Reporting Award three years in a row in 2007-2011. Data collecting research samples can be accessed through the company's website and the website of the National Sustainability Reporting Center and the company that publishes the Annual Financial Report for 2004-2014 which can be accessed through the company's website. Hypothesis testing is done by using paired sample t-test using IBM SPSS version 20 software. The results show that there are no differences between companies before and after being reported in the Indonesian Sustainability Reporting Report.